Analysis of the protein network of cholesterol homeostasis in different brain regions: An age and sex dependent perspective. Issue 7 (21st March 2013) - Segatto, Marco; Di Giovanni, Annalaura; Marino, Maria; Pallottini, Valentina
Abstract Although a great knowledge about the patho‐physiological roles of cholesterol metabolism perturbation in several organs has been reached, scarce information is available on the regulation of cholesterol homeostasis in the brain where this lipid is involved in the maintenance of several of neuronal processes. Currently, no study is available in literature dealing how and if sex and age may modulate the major proteins involved in the regulatory network of cholesterol levels in different brain regions. Here, we investigated the behavior of 3‐hydroxy 3‐methylglutaryl coenzyme A reductase (HMGR) and low‐density lipoprotein receptor (LDLr) in adult (3‐month‐old) and aged (12‐month‐old) male and female rats. The analyses were performed in four different brain regions: cortex, brain stem, hippocampus, and cerebellum which represent brain areas characterized by different neuronal cell types, metabolism, cytoarchitecture and white matter composition. The results show that in hippocampus HMGR is lower (30%) in adult female rats than in age‐matched males. Differences in LDLr expression are also observable in old females with respect to age‐matched males: the protein levels increase (40%) in hippocampus and decrease (20%) in cortex, displaying different mechanisms of regulation. The mechanism underlying the observed modifications are ascribable to Insig‐1 and SREBP‐1 modulation. The obtained data demonstrate that age‐ and sex‐related differences in cholesterol homeostasis maintenance exist among brain regions, such as the hippocampus and the prefrontal cortex, important for learning, memory and affection. Some of these differences could be at the root of marked gender disparities observed in clinical disease incidence, manifestation, and prognosis. J. Cell. Physiol. 228: 1561–1567, 2013. © 2012 Wiley Periodicals, Inc.